A Novel Technique of Ultrasound-Guided Selective Mandibular Nerve Block With a Lateral Pterygoid Plate Approach: A Cadaveric Study. Issue 7 (1st October 2018) - Kampitak, Wirinaree; Tansatit, Tanvaa; Shibata, Yasuyuki
Abstract : Background and Objectives: We aimed to describe a novel technique of ultrasound-guided selective mandibular nerve block with a lateral pterygoid plate (LPP) approach and to assess its feasibility and accuracy in a soft cadaver model. Methods: Ten soft cadavers were studied. A curved array ultrasound transducer was applied over 1 side of the face of the cadaver, in an open-mouth position. The transducer was placed transversely below the zygomatic arch and tilted in the caudal-to-cranial direction to identify the boundary of the LPP. The needle was inserted in-plane, in an anterior-to-posterior direction, into the posterior border of the uppermost part of the LPP, and 3 mL of methylene blue was injected. Results: Mandibular nerve block was successfully performed in all 10 cadavers using an LPP approach under ultrasound guidance. The mandibular nerve and its branches were seen to be stained with methylene blue in all cadaveric specimens. No accidental injection into the facial nerve or maxillary artery was observed. Conclusions: This cadaveric study suggests that this novel technique, using an LPP approach under ultrasound guidance, is helpful for selective mandibular nerve block, with high accuracy and feasibility. Further studies are required to establish its safety and efficacy for clinical application. Clinical Trial Registration: This study was registered at the Thai Clinical Trials Registry (ClinicalTrials.in.th), identifier TCTR20160601004.